Analisis Keuntungan Maksimum Penjualan Sendal dan Sepatu Toko Iksan di Kelurahan Siranindi - Adhwa Al Faatin; Muhammad Agung Ananta Praja; Moh Naif; Ario Ario; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
In the business world, particularly in the retail sector, market dynamics demand entrepreneurs to continuously adapt to sustain their businesses and maximize profits. However, this presents major challenges, including limited innovation in product design and the lack of utilization of social media as a marketing tool. This research aims to analyze the challenges and opportunities faced by Toko Iksan, which operates in the sale of sandals and shoes in Kelurahan Siranindi. The research method employs a qualitative descriptive approach through semi-structured interviews with the business owner and direct observation. The research results indicate that Toko Iksan faces significant challenges, such as increasing local competition, changes in consumption patterns due to online shopping trends, and limited capital. Business revenue mostly only covers operational needs without room for development. However, there is significant potential to enhance competitiveness through product design innovation, adoption of digital marketing, and market diversification. By utilizing digital technology such as social media and e-commerce platforms, as well as government support in training and access to capital, Toko Iksan can optimize profits and ensure business sustainability amidst increasingly intense competition